Labours of social inclusion: amateur, professional, community theatres. Issue 3 (1st September 2020) - Nicholson, Helen
ABSTRACT: This article is offered as a provocation into debates about how cultural hierarchies between amateur, professional and community theatres continue to resonate in contemporary British theatre. Building on research with amateur and community companies, this article presents a case for wider cultural recognition of the work of people in different sectors. It argues for greater reflexivity about the ways in which judgements of taste are played out, and asks who or what is legitimated, included and excluded in today's theatre. It asks how far there remains a link between distinctions of taste and divisions of labour, and what this might mean for theatre workers in the future.